Clot formation of neonates tested by thromboelastography correlates with gestational age - Strauss, Tzipi; Levy-Shraga, Yael; Ravid, Bruria; Schushan-Eisen, Irit; Maayan-Metzger, Ayala; Kuint, Jacob; Kenet, Gili (Thrombosis and Haemostasis, 2010)
Evaluation of clot formation in neonates is troublesome. Our aim was to investigate cord blood clot formation of pre-term versus full-term infants and adults, using rotating thromboelastogram (ROTEM®, Pentafarm, Munich, Germany). ROTEM was investigated in cord blood of 184 full-term and 47 pre-term infants. Measurements of the clotting time (CT), clot formation time (CFT) and maximal clot firmness (MCF) were obtained in order to asses reference values for this age group, and compare between full-term and pre-term neonates and compared to adult controls. For each infant demographic information and data regarding pregnancy and delivery were gathered. Infants were prospectively followed until discharge. CT and CFT were significantly shorter among pre-term and term infants as compared to adults [median CT: 185, 194, 293 seconds respectively, p≤0.001, CFT: 80, 76, 103 seconds respectively, p≤0.001). MCF was lower in pre-term and term as compared to adults (p≤0.001) with significantly lower values in pre-term as compared to full-term neonates (p=0.004). Clotting time and MCF correlated with gestational age (R=0.132, p=0.045, R= 0.259, p<0.001, respectively). No association was found between any ROTEM values and the occurrence of post-natal complications in infants of our study group. This is the first study assessing clot formation by ROTEM in pre-term infants. Clot formation parameters of term and premature infants correlated with gestational age. The predictive value of clot formation tests in neonates deserves further attention.
Keywords: Neonates; preterm; coagulation; thromboelastography; ROTEM